Social Relations, Capital, and Power in the Tobacco Industry: A Bourdieusian Practice Theory Perspective - Adhi, Rakhmat Nur; Sumitro , Sumitro; Utomo, Jepri; Febriani, Haniza (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
Social relations in the tobacco industry demonstrate an unequal relationship between farmers and other actors in the production and distribution chain. Farmers, as primary producers, are often in a weak position in determining prices and market access, thus relying on intermediaries such as middlemen and cigarette companies. This study aims to describe and analyze the social relations of tobacco farmers within the tobacco industry system using Pierre Bourdieu's theoretical perspective. This study employed a qualitative method with a case study approach. Informants were selected through purposive sampling involving six informants: four tobacco farmers and two intermediary actors in tobacco product distribution. Data collection was conducted through in-depth interviews, field observations, and documentation. The obtained data were analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results show that social relations in the tobacco industry form a structure that tends to benefit downstream actors. Middlemen and cigarette companies have stronger access to economic capital and marketing networks, thus playing a dominant role in determining prices and quality standards. Meanwhile, farmers have limited capital and access to information, leading to dependence on middlemen. This condition shapes a pattern of economic practices among farmers that tends to accept market prices without a balanced bargaining process. The discussion of this research confirms that social relations in the tobacco industry are not only influenced by market mechanisms, but also by social structures that reproduce the unequal position of farmers.